HUBUNGAN PENGETAHUAN STATUS GIZI, POLA MAKAN DAN PANTANGAN MAKANAN DENGAN KELANCARAN PRODUKSI ASI PADA IBU MENYUSUI DI PUSKESMAS WAY KANDIS KOTA BANDAR LAMPUNG TAHUN 2020 - Kadek Edy Artana Putra; Rilyani Rilyani; Lidya Ariyanti (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
THE CORRELATION BETWEEN KNOWLEDGE OF NUTRITIONAL STATUS, DIETARY PATTERNS AND DIETARY RESTRICTIONS WITH THE SMOOTH PRODUCTION OF BREAST MILK ON BREASTFEEDING MOTHERS AT WAY KANDIS COMMUNITY HEALTH CENTER, BANDAR LAMPUNG 2020Introduction: Based on health office of Bandar Lampung, 3 community health centreswith the lowest coverage of breastfeeding, such as, Way Kandis Community Health Centre, with 2730 children who received breastfeeding only 757 children, with a percentage of 31.94%, Panjang Community Health Centre, with 177 children who received breast milk only 61 children, with a percentage of 34.46%, Sukaraja Community Health Centre, with 317 children who received breast milk only 150 children, with a percentage of 47.32%. Purpose: It was known the correlation between knowledge, nutritional status, dietary pattern, and dietary restrictions with the smooth production of breast milk on breastfeeding mothers at Way Kandis Community Health Centre, Bandar Lampung 2020. Method:Quantitative research type, analytical survey research design by using cross sectional approach, population and sample was breastfeeding mothers as many 43 respondents, total sampling technique. Univariate and bivariate data analysis by using chi square test. Result: Frequency distributionknowledge of breastfeeding mothers in the poor category was 26 respondents (60.5%), the nutritional status of breastfeeding mothers in the poor category was 26 respondents (60.5%), the diet in the good category was 24 respondents (55.8%), dietary restriction category as many as 22 respondents (51.2%), the smooth production of breast milk mothers with less category was 18 respondents, p-value 0.004 <0.05, which means that there was a correlation between knowledge about breastfeeding and the smoothness of breast milk production, p-value 0.004 <0.05 which means that there was a correlation between nutritional status and the smooth production of breast milk in breastfeeding mothers, p-value 0.001 <0.05, which means there was a correlation between dietary pattern and the smooth production of breast milk for breastfeeding mothers, p-value 0.157 <0.05, which means there was a correlation between dietary restriction and smooth production of breast milk on breastfeeding mothers. It is hoped that mothers can increase milk production by increasing knowledge and consuming nutritious foods and maintaining a good diet. Keywords ; Knowledge, Nutritional Status, Dietary Pattern, Dietary Restriction, Smooth Production of Breast Milk HUBUNGAN PENGETAHUAN STATUS GIZI, POLA MAKAN DAN PANTANGAN MAKANAN DENGAN KELANCARAN PRODUKSI ASI PADA IBU MENYUSUI DI PUSKESMAS WAY KANDIS KOTA BANDAR LAMPUNG TAHUN 2020 Pendahuluan: Berdasarkan data dinas kesehatan Kota Bandar Lampung, 3 Puskesmas dengan cakupan pemberian ASI terendah yaitu, Puskesmas Way kandis, dengan jumlah anak 2.730 yang mendapat ASI hanya 757 anak, dengan persentase 31,94%, Puskesmas Panjang, dengan jumlah anak 177 yang mendapat ASI hanya 61 anak, dengan persentase 34,46%, Puskesmas Sukaraja, dengan jumlah anak 317 yang mendapat ASI hanya 150 anak, dengan persentase 47,32% Tujuan: Diketahui hubungan pengetahuan, status gizi, pola makan, pantangan makanan dengan kelancaran produksi ASI pada ibu menyusui di Puskesmas Way Kandis Kota Bandar Lampung Tahun 2020 Metode: Jenis penelitian kuantitatif, rancangan penelitian survey analitik pendekatan cross sectional, populasi dan sampel adalah ibu yang menyusui sebanyak 43 responden, teknik sampling total sampling,. Analisa data univariat dan bivariat mengguankan uji uji chisquare Hasil : Distribusi frekuensi pengetahuan ibu menyusui dengan kategori kurang baik sebanyak 26 responden (60,5%), status gizi ibu menyusui dengan kategori kurang baik sebanyak 26 responden (60,5%), pola makan dengan kategori baik sebanyak 24 responden (55,8%), pantang makan dengan kategori melakukan pantang makan sebanyak 22 responden (51,2%), kelancaran asi ibu menyusui dengan kategori kurang sebanyak 18 responden, p-value 0,004<0,05 yang artinya terdapat hubungan pengetahuan ibu tentang asi dengan kelancaran produksi ASI, p-value 0,004<0,05 yang artinya terdapat hubungan status gizi dengan kelancaran produksi asi pada ibu menyusui, p-value 0,001<0,05 yang artinya terdapat hubungan pola makan dengan kelancaran produksi asi pada ibu menyusui, p-value 0,157>0,05 yang artinya tidak terdapat hubungan pantang makan dengan kelancaran produksi ASI pada ibu menyusui. Diharpkan ibu dapat meningkatkan produkasi ASI dengan cara meningkatkan pengetahuan dan mengkomsumsi makanan bergizi serta menjaga pola makan yang baik